The Role of Genital Hiatus (Gh), Perineal Body (Pb), Summation (Gh+Pb) of POP-Q Examination in Maximum Levator Hiatal Area of Women with Symptomatic Pelvic Organ Prolapse - Kustarto, Kukuh W; Moegni, Fernandi (Indonesian Socety of Obstetrics and Gynecology, 2019)
Abstract Objective: to provide data on the correlation of levator hiatus area measurements in symptomatic POP using 3D / 4D Ultrasound with clinical examination of Gh, Pb and summation (Gh+Pb). Methods: Secondary data analysis of 160 POP patients examined from January 2012 to April 2017 at the Urogynecology Clinic RSCM, Jakarta. Taken data on patient characteristics, maximum 3D / 4D Ultrasound measurement of Levator Hiatus Area, and clinical measurement results using pelvic organ prolapse quantification system (POP-Q) Results: There was a positive correlation between clinical examination and measurement of hiatal area area using ultrasound with r = 0.43 for Gh length, and the medium correlation on the sum of Gh and Pb with r = 0,51. No correlation for Pb length with r = 0.23. The optimal cut to differentiate degrees 2 by 3 is 7.5 cm / 29.7 cm2 and degree 3 by 4 is 8.3 cm / 32.1 cm2. Conclusion: Clinical examination by summing the lengths of Gh and Pb may be consider reflects the examination of the hiatal area by using transperineal ultrasound to see the strain on levator ani called “ballooning” in an area with limited resources. Keywords:  genital hiatus, levator hiatus area, pelvic organ prolapse, perineal body.   Abstrak Tujuan: untuk memberikan data mengenai korelasi pengukuran area hiatus levator pada POP simtomatik mengunakan Ultrasonografi 3D/4D dengan pemeriksaan klinis yaitu panjang Gh, panjang Pb dan penjumlahannya. Metode : Analisa data sekunder sebanyak 160 pasien POP yang diperiksa dari Januari 2012 hingga April 2017 di poliklinik Urogynecology RSCM, Jakarta. Diambil data karakteristik pasien, pengukuran Ultrasonografi 3D/4D maksimal Area Hiatal Levator, dan hasil pengukuran secara klinis dengan menggunakan pelvic organ prolapse quantification system (POP-Q) Hasil : Terdapat korelasi positif antara pemeriksaan klinis dengan pengukuran luas area hiatal menggunakan USG dengan r = 0,43 untuk panjang Gh, dan korelasi pada penjumlahan Gh dan Pb dengan r=0,51 termasuk kategori sedang, sedangkan untuk panjang Pb dengan r = 0,23 tidak didapatkan adanya korelasi. Didapatkan titik potong optimal untuk membedakan derajat 2 dengan derajat 3 adalah 7,5 cm / 29,7 cm2 dan derajat 3 dan derajat 4 adalah 8,3 cm / 32,1 cm2 Kesimpulan : Pemeriksaan klinis dengan menjumlahkan panjang Gh dan panjang Pb dapat dipertimbangkan untuk mencerminkan pemeriksaan area hiatal dengan mengunakan USG 3 / 4 dimensi transperineal pada daerah dengan sarana terbatas untuk melihat regangan pada levator ani atau yang disebut sebagai “ballooning Kata kunci : badan perineum, genital hiatus, hiatal levator ani, prolaps organ panggul.